Abordarea conceptuală a inovaţiei în contextul relansării strategiei de la Lisabona - Stănescu, Simona Maria (Calitatea Vieții, 2009)
This article analyses the concept of social innovation. The first part approaches innovation in comparison with discovery and invention. The idea of new is included in all three concepts, only at different levels: at the output level, in the case of both discovery and invention, and at the process level, in the case of innovation. The second part overviews innovation within European Union and in our country, in the framework of implementing the Lisbon’s strategy. In comparison with other Member States, Romania’s innovative performance are the lowest, especially as regards knowledge, creation and intellectual property rights. Social innovation is presented in correlation with social development. The last part overviews factors that could stimulate social innovation.